1989
DOI: 10.1111/j.1365-2826.1989.tb00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Receptor Sites in the Syrian Hamster Brain and Pituitary. Localization and Characterization Using [125|]lodomelatonin*

Abstract: A high-affinity, discretely localized melatonin receptor has been characterized and mapped within the brain and pituitary of the Syrian hamster using the high specific activity ligand [ '251] In mammals, the pineal hormone melatonin is synthesized and secreted into the circulation with a precise nocturnal rhythm (I). The melatonin signal thus acts as an endocrine representation of the dark-phase (2). Melatonin has been shown to influence a variety of processes, including circadian cycles of activity in the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(67 citation statements)
references
References 37 publications
5
62
0
Order By: Relevance
“…It has been suggested that this may account for the inability of melatonin injections to entrain circadian activity rhythms in this species (24,25). In this study, and as described previously (17,18), the level of 2-[ 125 I]iodomelatonin binding in the SCN is much lower than in the PT (see Figs. 1 A and 3A), and, therefore, the difference in the Per1 and ICER responses to photoperiod may reflect differences in the sensitivity to melatonin.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It has been suggested that this may account for the inability of melatonin injections to entrain circadian activity rhythms in this species (24,25). In this study, and as described previously (17,18), the level of 2-[ 125 I]iodomelatonin binding in the SCN is much lower than in the PT (see Figs. 1 A and 3A), and, therefore, the difference in the Per1 and ICER responses to photoperiod may reflect differences in the sensitivity to melatonin.…”
Section: Discussionsupporting
confidence: 77%
“…Strong labeling by 2-[ 125 I]iodomelatonin, which is consistent with the localization of melatonin receptors, was observed in the PT and the SCN, but with a lower level of labeling in the SCN (Figs. 1 A and 3A), as described previously (17,18).…”
Section: Localization Of Per1 and Icer Expression In The Hamstermentioning
confidence: 99%
“…Iodomelatonin binding sites within the brains of control and compound infusion groups were identified as described previously (23). Rriefly, 20 pm cryostat sections were incubated with 100 pM ['251]iodomelatonin for 30 min at room temperature either alone or in the presence of 1 pM melatonin in Tris-HCI buffer.…”
Section: Autoradiographymentioning
confidence: 99%
“…Differences in the gonadal responses of animals to phasic or continuous exposure to melatonin could potentially be a consequence of reduced availability of the melatonin binding sites, resulting from occlusion of the melatonin-free interval. To determine whether such an effect could provide an explanation for differences in the responses to melatonin, the brains of animals were processed post-mortem for in vitro autoradiographic localization of iodomelatonin binding sites (23).…”
mentioning
confidence: 99%
“…In the present study, which employed subcutaneous melatonin implants in pineal-intact hamsters, the marked diurnal variation in serum melatonin titers was abolished as a consequence of elevated daytime levels, but rhythmicity in serum melatonin persisted (Figure 3). It must be stressed that melatonin has receptors in the SCN (Williams et al, 1989), and it is possible that, similar to the rhythm in melatonin release, SCN control of leptin release is mainly stimulatory; thus, removal of this stimulatory SCN control results in decreased leptin levels (Karakas and Gündüz, 2006). Choi and Dallman (1999) reported that in SCN-lesion rats, increased plasma leptin levels are accompanied by obesity.…”
Section: Discussionmentioning
confidence: 99%